Thermogravimetric analysis-based proximate analysis of agro-byproducts and prediction of calorific value. (November 2022) - Park, Sunyong; Kim, Seok Jun; Oh, Kwang Cheol; Cho, LaHoon; Jeon, YoungKwang; Lee, Chunggeon; Kim, DaeHyun
Abstract: Domestic agro-byproduct potential in Korea is estimated to be approximately 4, 018 × 10 3 tons of oil equivalent per year. Majority of agro-byproducts are unused and discarded. These unused agro-byproducts can potentially be converted into solid fuel for value addition. The energy potentials of solid fuels are generally characterized by proximate analysis and measuring calorific value; however, owing to the use of coal and coke, both the analyses could be expensive and time-consuming. Proximate analysis via thermogravimetric analysis is a relatively low cost and less time-consuming method than proximate analysis by ISO method (ISO 18134-1:2015, ISO 18123:2015, ISO 18122:2015). Thermogravimetric analysis-based proximate analysis of four agro-byproducts (pepper stem, perilla stem, corn stalk, and kenaf) was conducted. Additionally, the calorific values obtained from several equations based on the proximate analysis results were compared to that of the calorific value measured using calorimeter. The maximum difference between proximate analysis using thermogravimetric analysis and ISO method was 4.73%p, which was attributed to change in moisture content. It is recommended to measure the moisture content of biomass for 120–150 min (at 105 °C) and ash content for 80–120 min (at 815 °C). Three of the equations indicated a difference of less than 1.5 MJ kg −1 between the TGA-derived and the measured calorific value. For this study, It was determined that both proximate analysis and prediction calorific value can be conducted by thermogravimetric analysis.